Afirmasi Hukum Bagi Kelompok Disabilitas di Indonesia - Al Maslul, Husam El Haq; Ginanjar, Nana; Hidayat, Syarif; Andini, Sri; Harahap, Chisa Belinda (Gunung Djati Conference Series, 2025)
Discrimination is unequal treatment experienced by individuals or groups based on certain identities, including disability. This research uses a qualitative method with a literature study to explore discrimination against people with disabilities in Indonesia and the role of affirmative policies. The results show that although there are laws that guarantee the rights of people with disabilities, such as UU No. 8 Tahun 2016, implementation is still weak and discrimination persists in various sectors, including education and employment. The case of Romi Syofpa Ismael illustrates the challenges that persons with disabilities face in access to equal opportunities. This research recommends the need for reforms in affirmative policies, increased public awareness, and synergy between government and civil society to create a more inclusive and equitable environment for people with disabilities.